Factors influencing patient satisfaction with dental appearance and treatments they desire to improve aesthetics - Mon, Mon Tin Oo; Saddki, Norkhafizah; Hassan, Nurhidayati (BioMed Central, 2011)
Background: We assessed factors influencing patients’ satisfaction with their dental appearance and the treatments they desired to improve dental aesthetics. Methods: A cross-sectional study was performed out among 235 adult patients who visited the Hospital Universiti Sains Malaysia dental clinic. A structured, interviewer-guided questionnaire was used to identify patient satisfaction with their general dental appearance, cosmetic elements and desired treatments. Results: The 235 patients consisted of 70 males (29.8%) and 165 females (70.2%), of mean age 31.5 years (SD 13.0). Of these patients, 124 (52.8%) were not satisfied with their general dental appearance. In addition, 132 patients (56.2%) were not happy with the color of their teeth, 76 (32.3%), regarded their teeth were poorly aligned, 62 (26.4%), as crowded and 56 (23.4%) protruded. Dissatisfaction with tooth color was significantly higher in female than in male patients (odds ratio [OR] of 1.99 (95% confidence interval [CI] 1.13-3.50). Tooth whitening was the treatment most desired by patients (48.1%). Results of multiple logistic regression analysis showed that patient dissatisfaction with general dental appearance was significantly associated with female gender (OR = 2.18; 95% CI: 1.18-4.03), unhappiness with tooth color (OR = 3.05; 95% CI: 1.74-5.34) and the opinion that their teeth protruded (OR = 2.91, 95% CI: 1.44-5.91).